Over 100-Year Preservation and Temporal Fluctuations of Cell Wall Polysaccharides in Marine Sediments - Salmeán, Armando A.; Willats, William George Tycho; Ribeiro, Sofia; Andersen, Thorbjørn Joest; Ellegaard, Marianne (Frontiers in Plant Science, 2022)
Polysaccharides constitute an important carbon pool in marine systems, but much is still unknown about the fate and degradation of these compounds. They are derived partly from production in situ, and in coastal areas, they are partly terrestrially derived, originating from freshwater runoff from land. The aim of this study was to test the applicability of high-throughput polysaccharide profiling for plant and algal cell-wall compounds in dated sediment cores from a coastal marine environment, to examine the preservation of cell-wall polysaccharides and explore their potential as proxies for temporal environmental changes. Preserved compounds and remains of organisms are routinely used as paleoenvironmental proxies as the amount and composition of different compounds that can provide insight into past environmental conditions, and novel means for reporting environmental changes are highly sought.